Effect of different dielectric materials for ultrathin oxide - Zarimawaty Zailan
This final year project is about performance of ultrathin gate oxide using Silicon Nitride to replace the Silicon Dioxide as dielectric materials and use the Synopsys's Taurus TCAD tools to fabricate virtual semiconductor devices as a virtual fabrication environment.